The role of age, neutrophil infiltration and antibiotics timing in the severity of streptococcus pneumoniae pneumonia. Insights from a multi-level mathematical model approach - Santos, Guido; Vera, Julio (International Journal of Molecular Sciences, 2020)
Bacterial pneumonia is one of the most prevalent infectious diseases and has high mortality in sensitive patients (children, elderly and immunocompromised). Although an infection, the disease alters the alveolar epithelium homeostasis and hinders normal breathing, often with fatal consequences. A special case is hospitalized aged patients, which present a high risk of infection and death because of the community acquired version of the Streptococcus pneumoniae pneumonia. There is evidence that early antibiotics treatment decreases the inflammatory response during pneumonia. Here, we investigate mechanistically this strategy using a multi-level mathematical model, which describes the 24 first hours after infection of a single alveolus from the key signaling networks behind activation of the epithelium to the dynamics of the local immune response. With the model, we simulated pneumonia in aged and young patients subjected to different antibiotics timing. The results show that providing antibiotics to elderly patients 8 h in advance compared to young patients restores in aged individuals the effective response seen in young ones. This result suggests the use of early, probably prophylactic, antibiotics treatment in aged hospitalized people with high risk of pneumonia.
CRIS-Team Scopus Importer:2020-11-20
Keywords: Inflammation; Macrophages; Mathematical model; Monocytes; Multi-level; Neutrophils; Pneumonia; Streptococcus pneumoniae